Bias assisted scanning probe microscopy direct write lithography enables local oxygen enrichment of lanthanum cuprates thin films. (24th July 2015) - Lavini, Francesco; Yang, Nan; Vasudevan, Rama K; Strelcov, E; Jesse, S; Okatan, M B; Kravchenko, I; Di Castro, Daniele; Kalinin, Sergei V; Balestrino, Giuseppe; Aruta, Carmela; Foglietti, Vittorio
Abstract: Scanning probe bias techniques have been used as a method to locally dope thin epitaxial films of La2 CuO4 (LCO) fabricated by pulsed laser deposition. The local electrochemical oxidation of LCO very efficiently introduces interstitial oxygen defects in the thin film. Details on the influence of the tip voltage bias and environmental conditions on the surface morphology have been investigated. The results show that a local uptake of oxygen occurs in the oxidized films.